Digital Forensik sebagai Penegakan Hukum pada Kasus Fraud COD dalam Industri Logistik - Syifa Qurrota Ayuni Rizqi (Jurnal Hukum Lex Generalis, 2025)
This research aims to examine the role of digital forensics in law enforcement efforts related to fraud committed by couriers in the logistics sector, particularly in Cash-on-Delivery (COD) schemes. The research method used is qualitative with a case study approach, through in-depth interviews with relevant parties, as well as analysis of the perpetrators' devices, company systems, and other digital evidence. The results of the study indicate that the use of digital forensics can accelerate the investigation process and increasing accuracy in proving cases, thereby supporting a more transparent and fair law enforcement system. The implementation of digital forensics is expected to minimize fraudulent acts within the logistics industry and provide better protection for both consumers and businesses.